Integrasi Media Sosial Dalam Pembelajaran Pendidikan Kewarganegaraan : Dampak Terhadap Partisipasi dan Pemahaman Peserta Didik - Randi, Muhammad Sinar; Syafiq, Hilmi Atha; Mudya, Yalfina; Anggring, Sintia Dwi; Ritonga, Farihatul Ula (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to explore the impact of social media integration, participation and understanding of students in learning civic education, as well as recommendations for educators and policy makers in designing innovative learning strategies that are relevant to the needs of the times. It is hoped that using social media can make the learning atmosphere collaborative and dynamic. Using the literature study method, this research examines various relevant sources to analyze how social media platforms can be used as effective learning tools. The results of this study show that optimizing civic education through social media can be done by utilizing various types of social media, creating creative and innovative content, and following accounts that provide national insight. Thus, civic education can be more effective and respond to the needs of the whole community. In conclusion, the use of social media in civic education needs to be continuously developed to improve learning effectiveness. Collaboration between technology and education is key to making learning more engaging and effective for learners, and to help shape smart and ethical citizens in the digital era.